Munculnya Lembaga Pendidikan Islam - Asna Andriani (STAIFAS-Press, 2016)
Islam gives high spirit to itsÂ dherents or followers for searching of knowledge, even after the Prophet's death, Islamic education has developed very rapidly both in the aspect of curriculum and educational institutions. This condition is caused by the Islamic community has developed increasingly complex, both in the number of its adherents are growing as well as the condition of the Islamic territory, Thus the needs for education has increased so appear agencies as a form of institutionalized tradition of science and learning in Islam, ranging from the simplest until that can be regarded as modern models of learning, so that eventually emerge in the next era of Islamic development as places of learning in Muslim society. Â Kata Kunci: Sejarah munculnya, Lembaga pendidikan Islam